Intentional Training With Speech Production Supports Children’s Learning the Meanings of Foreign Words: A Comparison of Four Learning Tasks - Junttila, Katja; Ylinen, Sari (Frontiers in Psychology, 2020)
To determine the best techniques to teach foreign words to children, we compared the effectiveness of four different learning tasks on children’s foreign word learning (i.e., the learning of word forms and word meanings). The tasks included incidental learning, intentional learning with production, intentional learning without production, and cross-situational statistical learning. We also tested whether children’s age and cognitive skills correlate with the learning of word forms and word meanings. Forty-four 5-8-year-old children participated in the study. The results show that the children were able to learn the correct word forms with all four tasks and no differences between the effectiveness of the tasks were found on word-form learning. The children also learned the word meanings with all four tasks, yet intentional task with production was more effective than incidental task. This suggests that children’s foreign-word learning benefitted from knowing that they were supposed to learn new words and producing them aloud while training. Children’s age correlated with learning results for word forms and meanings in intentional task without production. Learning was more effective in older than in younger children in this task. Children’s phonological processing skills were correlated with learning the word meanings with incidental task, suggesting that children with better phonological skills were able to benefit from incidental learning more than children with poorer phonological skills. Taken together, the results suggest that children’s foreign-language learning benefits from intentional training with speech production regardless of age or cognitive skills.